Studies of a glow discharge electron beam - Rocca, Jorge J., author; Yu, Zengqi, author; Collins, George J., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1983)
The energy spectrum of a kilovolt electron beam, generated by a helium glow discharge at pressures between 0.15 and 0.8 Torr, was measured with an electrostatic energy analyzer. An abrupt increase in the energy spread of the electron beam was observed to be coincident with an increase in the luminosity of the electron beam created plasma, and with the onset of intense microwave radiation. The relevance of these phenomena in cw electron beam pumped ion lasers is discussed.